Philippine Scleractinian corals, additional records - Nemenzo, Francisco; Hodgson, Gregor (1983)
Twenty-one species of scleractinian corals collected from 8 stations in the Central Visayas and Mindoro using SCUBA are described. Sixteen are new distributional records for the Philippines. Several are are or hemisciaphilic species. Preliminary evidence is presented in support of combining the two genera Physogyra and Plerogytra into one.